A climatology of tornadic activity over Greece based on historical records - Matsangouras, I. T.; Nastos, P. T.; Bluestein, H. B.; Sioutas, M. V. (International Journal of Climatology, 2014)
In this study, the climatology of tornadoes, waterspouts and funnel clouds over Greece is presented for the period 1709-2012. The climatology consists of two datasets. An historical dataset (1709-1999) is based on newspaper archives, historical archives, published tornado literature, administrative records and reports of Hellenic National Meteorological Service (HNMS). A recent dataset (2000-2012) is based on newspaper articles, eyewitness reports to the media, HNMS's reports and an open-ended online tornado report database which has been developed and maintained by the Laboratory of Climatology & Atmospheric Environment of the University of Athens. Altogether, 612 Greek tornadic events compose the climatology: 171 tornadoes, 374 waterspouts and 67 funnel clouds. Tornadic events during the past 13years (2000-2012) have occurred all over the Greek territory and there is frequent tornadic occurrence over north Crete and Corfu Island. Tornadoes are more frequent to occur over NW Peloponnesus followed by south parts of Corfu Island. However, waterspouts are more frequent over north Crete followed by Corfu Island. Tornadic monthly variability depicts a maximum during October, followed by September and November. October is the month with the highest tornado frequency, followed by November and July. The highest waterspout frequency month is September followed by October and December. Tornadoes most commonly develop during the warm time of the day, as more than 75% of all cases occur during 08:00-15:00hours UTC with a maximum at 12:00hours UTC. Waterspout frequency of occurrence has two maxima during the day, the first early in the morning (07:00-09:00hours UTC) and the second after the noon time period (14:00-15:00hours UTC). The dominant (27.7% of total cases) intensity of tornadoes in Greece is T4 based on the T-scale during the 300-year period (1709-2012); there have been at least 114 injured and 29 deaths. © 2013 Royal Meteorological Society.
Keywords: Atmospheric environment; Climatology; cloud; Funnel clouds; Greece; Historical archive; Historical dataset; historical record; Historical records; NCEP-NCAR reanalysis; Newsprint; Reanalysis; Time-periods; tornado; Tornadoes; waterspout; Waterspouts